2001
DOI: 10.1055/s-2001-11421
|View full text |Cite
|
Sign up to set email alerts
|

α-Phosphonovinyl Carbanions in Organic Synthesis

Abstract: The generation of several a-phosphono-substituted vinyl carbanions is described. The a-phosphonovinyl carbanions have been used to afford versatile vinylphosphonate reagents capable of a wide range of synthetic transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The only review covering this area was written by Minami 2 and was published in 1992. Several reviews on vinylphosphonates, [3][4][5] published later on, did not deal with Michael additions. Only very recently was the application of 1-phosphorus-functionalized 1-sulfur-functionalized alk-1-enes in organic synthesis, including their role as Michael acceptors, reviewed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The only review covering this area was written by Minami 2 and was published in 1992. Several reviews on vinylphosphonates, [3][4][5] published later on, did not deal with Michael additions. Only very recently was the application of 1-phosphorus-functionalized 1-sulfur-functionalized alk-1-enes in organic synthesis, including their role as Michael acceptors, reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The described methodology was also applied to the synthesis of enantiomerically pure cyclopropylphosphonate analogues of nucleotides. 15 The usefulness of vinylphosphonates in the development of a convenient synthetic route to cyclopentanoid frameworks was demonstrated by Minami et al 16,17 who reported the synthesis of tricyclo[6.3.0.0 3,7 ]undecenones 34a-c, which are terpenoids with potential antibacterial and anticancer activity. The starting b-keto vinylphosphonates 29a-c were prepared by the two methods presented in Scheme 7.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Their preparation is varied. 3,4 Recently, we have shown that it is possible to zirconate 1-alkynylphosphonates 5 with ZrCp 2 Cl 2 -n-BuLi, 6 (1:2) to give three-member phosphonate zircona-cycles. 7 The zirconacycles undergo insertion reactions with alkynes 7 and aldehydes 8 to provide, after hydrolysis, substituted vinyl phosphonates not available by other routes (Scheme 1).…”
mentioning
confidence: 99%